Sistema de control interno de inventarios para la disminución del riesgo de fraudes en las MIPYMES pequeña importadora - Coronel Molina, Paola del Carmen (2021)
The research is entitled "Internal inventory control system to reduce the risk of fraud in small importing SMEs", whose general objective was to evaluate the internal control of inventories and its influence on reducing the frequency of any type of fraud in the business during 2018 and 2019. Since there are countless deficiencies that merit investigation. An analysis with a quantitative and qualitative approach was established that was supported by different analysis tools that allowed us to know the dimension of the effects of these deficiencies in economic terms. It is provided with qualitative and quantitative results that will be used to design a corrective plan. A technical report was developed where the main results found are presented. It is concluded that the idea to be defended is valid, since the lack or deficiencies in the controls have a significant impact on the accounting results of the study company……………